Weekday Wellness: Integrating Wellness into an Educational Curriculum [5O]. (May 2018) - Chang, Katherine; Hall, Evelyn; Gorrindo, Phillip; Gerber, Susan
Abstract : INTRODUCTION: Residencies work to balance the demands of training, service, education, and wellness. The ACGME has recognized the importance of trainee wellness, and a new emphasis has been placed on this topic. Prior literature describes burnout rates of >50% among OB/GYN residents. It is important to better quantify the rates of burnout among OB/GYN trainees and develop initiatives to meaningfully impact burnout. METHODS: We administered an anonymous, mixed-methods residency-wide survey to obtain opinions about our proposed Wellness Initiative and to gather baseline data using the WHO Well-Being Survey and the Maslach Abbreviated Burnout Inventory. Quantitative results were analyzed with descriptive statistics. Qualitative results were coded by two independent reviewers and relevant themes were developed. RESULTS: 27/47 residents responded to the survey (57%). Of these, 48% met criteria for burnout and 67% had low mood or depression. Most residents supported this Wellness Initiative (96%), felt it would improve overall resident wellness (74%), and did not feel it would negatively impact education (96%). Themes identified include: optimism among interns, depersonalization and emotional exhaustion attributed to lack of personal time among senior trainees. CONCLUSION: Rates of overall burnout increase with each postgraduate year. Within the subscales of burnout, emotional exhaustion is most significantly affected while personal accomplishment remains high. Creative ways of integrating activities that strengthen resilience into an educational curriculum are needed to improve resident wellness and impact high rates of OB/GYN resident burnout.